Suitable conditions for sealing of open dentinal tubules using a pulsed Nd:YAG laser - Zapletalová, Zdeňka; Peřina, Jan; Novotný, Radko; Chmelíčková, Hana (Photomedicine and laser surgery, 2007)
BACKGROUND DATA AND OBJECTIVES: Nd:YAG laser radiation has been applied in treatment of dentine hypersensitivity; dentine melt created after irradiation on a tooth surface can occlude open dentinal tubules. Different conditions (energy of pulses, number of successive irradiations, and type of dye agent) have been reported in the literature. In our study, different conditions are compared and the most suitable ones are suggested. METHODS: One hundred nine dentine samples prepared from extracted human third molars in the form of 2- or 3-mm thick discs and facets from an outer convex surface of a root were irradiated by pulses with duration 0.3 ms and beam diameter 0.3 or 0.6 mm. The laser repetition rate was 15 Hz. Energies per pulse have been changed from 20 mJ to 250 mJ (the corresponding energy densities rho are 22 and 275 J/cm(2) for the beam diameter of 0.3 mm). Dyes including tartrazine, carmine indigo, erythrosin, and methylene blue have been used to cover dentine surfaces and to increase absorption of laser radiation. Irradiated dentine surfaces have been investigated using scanning electron microscopy. RESULTS: Sealing of open dentinal tubules can be accomplished even without dyes, provided that a sufficiently intense laser radiation level is used. To avoid damage to the dentine's surface the use of dyes is necessary. Erythrosin has been found to be the best agent, and closing of dentinal tubules occurred after four doses of irradiation with 30-mJ pulses with a beam diameter of 0.6 mm (energy density rho = 8.25 J/cm(2), total energy density rho(T) = 33 J/cm(2)). The upper limit has been reached using four doses of irradiation by 90-mJ pulses with a beam diameter of 0.3 mm (rho = 99 J/cm(2), rho(T) = 396 J/cm(2)). CONCLUSIONS: Occluding dentinal tubules can safely and effectively be accomplished using pulsed Nd:YAG laser radiation provided that the dentine surface is covered with erythrosin solution.
Keywords: financování organizované; Fluorescent Dyes; erythrosin; Neodymium; Microscopy, Electron, Scanning; Dentin Sensitivity; In Vitro Techniques; techniky in vitro; lidé; mikroskopie elektronová rastrovací; Erythrosine; fluorescenční barviva; Dentin Permeability; Dentin; Financing, Organized; dentin; permeabilita dentinu; neodym; citlivost dentinu; laserová terapie; Laser Therapy; Humans